Long-standing Persistent Atrial Fibrillation Ablation in a Patient With High Risk of Bleeding - Pisani, Cristiano; Chokr, Muhieddine; Hardy, Carina; Lara, Sissy; Scanavacca, Mauricio (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
A 57 year-old patient with dilated cardiomyopathy, long-standing persistent atrial fibrillation, heart failure and episodes of gastrointestinal bleeding underwent AF ablation with pulmonary vein isolation, homogeneization of septal scar, posterior wall isolation and also left atrial appendage isolation. Additionally, because of the high risk of embolism, underwent left atrial appendage occlusion.